Cloning, Sequencing and Expression of an Organic Solvent Tolerant Protease from Bacillus Pumilus 115B - Mahamad, Shalihah (2006)
Five out of the nine isolated bacteria species screened earlier, demonstrated high protease production on Skim Milk Agar and were also to Benzene Toulene Xylene Ethylbenzene (BTEX). Among these, isolate 115b was found to produce the highest protease production. Besides being stable in 25% (v/v) benzene and toluene, protease from isolate 115b was found to be activated by n-dodecane and n-tetradecane by 1.7 and 2.5 folds respectively. Isolate 115b was identified as Bacillus pumilus 115b via biochemical tests and 16S rDNA sequencing analysis.